Dramawebben (demo) - Språkbanken Text (University of Gothenburg, 2024)
Texts from Dramawebben, a digital archive of free Swedish drama.

Texter från Dramawebben, ett digitalt arkiv över fri svensk dramatik.
Dramawebben (demo)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik